Analysis of reliability prediction and maintainability activities of an earth station system using parallel configurations - Abdul Rahman, Nur Shazana; Abdul Rahim, Nadirah (International Workshop on Computer Science and Engineering, 2022)
The recent news regarding the Malaysian satellite, MEASAT-3; which suffered an anomaly has caused the satellite to drift out of its geostationary orbit, and the uncontrolled re-entry of the Chinese Long March 5B rocket in 2021 had sparked high alarms in satellite operators industry. Due to the satellite communication system failure, the government had loss a massive amount of money. Hence, it is essential to equip the system with a sustainable framework design which can be achieved through an optimum system reliability and maintainability. Subsystem redundancies, multiple testing during the planning stage, and selection of only the best components for its subsystems can improve the system reliability. Also, relevant maintenance activities should be performed frequently to avoid cost overruns and unforeseen failures. This paper presents an analysis of the reliability and maintainability of an Earth Station system using Monte Carlo simulations. The results show that the highest reliability value is obtained for the 3-parallel configuration. Suitable maintenance activities are also suggested to assist with the maintainability of the Earth Station system.